The Times They Are A-Changing? Exploring the potential shift away from the neoliberal political-economic paradigm - Laurie Laybourn-Langton; Laurie Macfarlane; Michael Jacobs (Forum for a New Economy, 2019)
Modern economic history can be roughly split into different eras in which certain sets of ideas dominate politics and policy-making. This paper seeks to understand if a shift in the 'political economic paradigm' is currently under way by inspecting the state of debates across a range of economic policy areas. It introduces the concept of 'orthodox', 'modified' and 'alternative' paradigms, corresponding to the status quo, its modification in the face of disruption or changed political goals, and a fundamental break from that status quo, respectively. Its central conclusion is that a significant shift is under way in many economic policy areas in many mainstream economic institutions. This shift has mainly occurred from 'orthodox' paradigm approaches – those that might broadly be described as based on neoclassical principles – to a 'modified' approach that alters the neoclassical approach in many ways but maintains its fundamental basis. Little to no movement towards what might be described as truly 'alternative' paradigm approaches is yet under way, though some mainstream institutions are exhibiting openness to these ideas. As such, an overall paradigm shift away from the dominant neoliberal paradigm is not yet underway. – – Die moderne Wirtschaftsgeschichte lässt sich grob in verschiedene Epochen unterteilen, in denen bestimmte Vorstellungen die Politik und die politischen Entscheidungen dominieren. In diesem Papier wird versucht zu verstehen, ob derzeit ein Wechsel des "politisch-ökonomischen Paradigmas" stattfindet, indem der Stand der Debatten in einer Reihe von wirtschaftspolitischen Bereichen untersucht wird. Es wird das Konzept des "orthodoxen", des "modifizierten" und des "alternativen" Paradigmas eingeführt, das dem Status quo, seiner Modifizierung angesichts von Störungen oder veränderten politischen Zielen bzw. einem grundlegenden Bruch mit diesem Status quo entspricht. Die zentrale Schlussfolgerung ist, dass in vielen wirtschaftspolitischen Bereichen und in vielen etablierten Wirtschaftsinstitutionen ein signifikanter Wandel im Gange ist. Dieser Wandel vollzieht sich hauptsächlich von "orthodoxen" paradigmatischen Ansätzen – d. h. solchen, die im Großen und Ganzen als auf neoklassischen Grundsätzen beruhend beschrieben werden können – hin zu einem "modifizierten" Ansatz, der den neoklassischen Ansatz in vielerlei Hinsicht abändert, aber seine grundlegende Basis beibehält. Es gibt noch wenig bis gar keine Bewegung in Richtung dessen, was man als wirklich "alternative" Paradigmenansätze bezeichnen könnte, auch wenn einige Mainstream-Institutionen Offenheit für diese Ideen zeigen. Ein allgemeiner Paradigmenwechsel weg vom vorherrschenden neoliberalen Paradigma ist also noch nicht im Gange.
Keywords: B20; B25; E00; H10; P16; P50; 330; political-economic paradigm; neoliberalism; heterodox economics